The Effectiveness of YouTube-Based Basketball Learning - Rahmadani, Ahmad; Candra, Oki; Daharis, Daharis; Fauzi, Muhammad (Indonesian Journal of Sport Management, 2024)
This study assesses how well YouTube is a learning tool for developing fundamental basketball abilities. As more people turn to digital platforms, YouTube has become popular as a resource for sports skill development. In this study, 30 individuals were split into two groups using a quasi-experimental design: 15 participants in the experimental group (n = 15) watched YouTube videos, and 15 participants in the control group (n = 15) employed traditional training techniques. Assessments of fundamental abilities such as dribbling, passing, and shooting were conducted six weeks before and after the intervention. According to the data, the experimental group outperformed the control group in fundamental basketball abilities. The average basic skills score in the experimental group went from 61.4 to 86.8, whereas in the control group, it only went from 57.8 to 74.6. The t-test statistical analysis demonstrates the significance of this rise (p < 0.01). Furthermore, regression analysis results indicate that the frequency of practice ( = 0.47, p 0.05) and time spent watching training videos ( = 0.42, p 0.05) positively impact skill development. These results imply that YouTube can be useful for learning basketball, particularly for novices who need access to official instruction. Nevertheless, the short intervention period and the study's focus on inexperienced individuals prevented a thorough analysis of other factors, including participant motivation and the calibre of the video content. Future research is advised to examine the long-term efficacy of YouTube-based learning and the effects of other factors, including the tutorials' calibre and interaction with virtual teachers.